Optimising Child-Friendly Districts: Overcoming Challenges in West Aceh Regency - Fitriah Hildhah; Vellayati Hajad; Herizal; Ikhsan; Distya Setyaningsih (Soshum: Jurnal Sosial dan Humaniora, 2025)
This study evaluates the role of the Women's Empowerment, Child Protection, and Family Planning Service in implementing the Child-Friendly Areas concept in West Aceh Regency, as mandated by the West Aceh Regent Regulation Number 40 of 2018. Using a descriptive qualitative method, data were collected through observations, interviews, and documentation with six informants. Findings indicate that while the policy aspect has been implemented optimally, the strategy and communication roles have not been effective. Key obstacles include insufficient human resources, facilities, budget, and inter-organizational communication. Additionally, public awareness of the Child-Friendly District status remains low. Despite ongoing efforts, significant improvements are needed to achieve optimal implementation.